Bioinspired Liquid‐Free Ion‐Conductive Elastomers with Ultrahigh Mechanical Strength and Excellent Ionic Conductivity for Multifunctional Flexible Sensing Applications - Zequan Li; Jingjing Tang; Xuwei Wang; Fuqi Wang; Fangyan Ou; Wenyu Pan; Changsheng Wang; Ting Xie; Chuang Ning; Xiwei Xu; Jiamin Liu; Qihua Liang; et al. (Advanced Science)
Abstract Liquid‐free ion‐conductive elastomers with excellent mechanical and electrical conductivity are widely used in flexible sensors, wearable devices, soft touch screens, and supercapacitors. However, the inherent contradiction between mechanical and electrical properties often limits the development of liquid‐free ion‐conductive elastomers. Therefore, the preparation of liquid‐free ion‐conductive elastomers with both high mechanical properties and high ionic conductivity remains a major challenge. In this study, a polyurethane elastomer with multiple crosslinking and a microphase‐separated structures were designed, inspired by the “brick wall” structure of the pearl layer. A polyurethane‐based liquid‐free ion‐conductive elastomer with excellent mechanical strength and outstanding ion‐conducting properties was prepared by introducing lithium bis(trifluoromethane)sulfoximide (LiTFSI) into the polyurethane elastomer. FLICE‐110% liquid‐free ion‐conductive elastomer had excellent mechanical strength (5.46 MPa), exceptional elongation at break (1213%), excellent ionic conductivity (3.29 × 10−4 S cm−1), and excellent fracture energy (6.25 kJ m−2). Flexible sensors prepared based on FLICE‐110% liquid‐free ion‐conductive elastomer have realized applications in wearable devices, multi‐channel strain sensors, and remote‐controlled robots. In addition, we successfully recovered LiTFSI from FLICE‐110% liquid‐free ion‐conductive elastomer. The development of these liquid‐free ion‐conductive elastomers will be expected to show a wide range of applications in flexible sensors, ionic skin, soft robotics, and human‐machine interactions.